Subtractive-Catastrophic Xenophilia - Roden, David (Identities: Journal for Politics, Gender and Culture, 2019)
Subtraction is a critical method whereby a cognitively inaccessible reality is thought in terms of its inaccessibility or “subtraction” from discourse. In this essay I begin by considering the role of subtraction in Alain Badiou’s work, where the method receives its most explicit contemporary articulation. I then generalize subtraction beyond Badiou’s ontology to explore a productive aporia in posthumanist theory. The implicit subtraction of posthumanist epistemology and ontology, I claim, confronts theorists of the posthuman with an inescapable tension between their philosophical language and its deployment within the historical situation I call the “posthumanist predicament.” This reveals an equivalence between ontological subtraction and an empty compulsion to become what one cannot yet think, or “xenophilia.” That is, between a philosophy of limits that forecloses the thought of the posthuman (qua defined structure or subject) through subtraction and an implicit desire to construct or “become” this subtracted, unpresented posthuman. Author(s): David Roden Title (English): Subtractive-Catastrophic Xenophilia Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 16, No. 1-2 (Summer - Winter 2019) Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 40-46 Page Count: 7 Citation (English): David Roden, “Subtractive-Catastrophic Xenophilia,” Identities: Journal for Politics, Gender and Culture, Vol. 16, No. 1-2 (Summer - Winter 2019): 40-46.